Systematic Review of the Effects of Body Temperature on Outcome Following Adult Traumatic Brain Injury - Madden, Lori Kennedy (J Neurosci Nurs, 2015)
OBJECTIVE: This systematic review describes effects of body temperature alterations defined as fever, controlled normothermia, and spontaneous or induced hypothermia on outcome following traumatic brain injury (TBI) in adults. DATA SOURCES: A search was conducted using PubMed, Cochrane Library database, CINAHL, EMBASE, and ISI Web of Science in July 2013 with no back date restriction except for induced hypothermia (2009). STUDY SELECTION: Of 1366 titles identified, 712 were reviewed. Sixteen articles met inclusion criteria: Randomized Controlled Trials (RCT) in hypothermia since 2009 (last Cochrane review) or cohort studies of temperature in TBI; measure core and/or brain temperature; neurologic outcome reporting; primarily adult patients, and English language publications. Exclusion criteria: majority of patients were non-TBI, primarily pediatric patients, case reports, or lab/animal studies. DATA SYNTHESIS: The majority of studies found that fever avoidance resulted in positive outcomes including: decreased intensive care unit length of stay, mortality; and incidence of hypertension, elevated intracranial pressure, and tachycardia. Hypothermia on admission correlated with poor outcomes. Controlled normothermia improved surrogate outcomes. Prophylactic induced hypothermia is not supported by the available evidence from RCT. CONCLUSION: Setting a goal of normothermia, avoiding fever, and aggressively treating fever may be most important after TBI. Further research is needed to: characterize the magnitude and duration of temperature alteration after TBI; determine if temperature alteration influences or predicts neurologic outcome; determine if rate of temperature change influences or predicts neurologic outcome; and compare controlled normothermia versus standard practice or hypothermia.